2012
DOI: 10.1074/jbc.m111.330910
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Involvement of O-GlcNAc-modified Human RNA Polymerase II CTD in Transcription in Vitro and in Vivo

Abstract: Background: Modifications of the RNA polymerase II CTD are necessary for transcriptional regulation. Results: Perturbation of O-GlcNAc addition and removal showed transcription defects in vitro and in vivo. Conclusion: O-GlcNAc modification of the CTD functions in transcription initiation.Significance: These data provide an additional modification of the CTD that acts before the initiation of transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(176 citation statements)
references
References 55 publications
11
165
0
Order By: Relevance
“…7A, the OGT inhibitor suppressed nascent RNA synthesis in T cells cultured on anti-CD3/CD28-coated coverslips, as measured by metabolic incorporation of a uridine analog. Although this result is consistent with the notion that O-GlcNAc directly affects the activity of RNA polymerase, transcription factors, or epigenetic regulators (63,64), the observed decrease in labeling may also arise indirectly from a defect in T cell activation, which normally leads to increased RNA synthesis (65). Thus, we repeated this experiment using flow cytometry to enable the analysis of resting T cells.…”
Section: Inhibition Of Ogt Blocks Rna Synthesissupporting
confidence: 85%
“…7A, the OGT inhibitor suppressed nascent RNA synthesis in T cells cultured on anti-CD3/CD28-coated coverslips, as measured by metabolic incorporation of a uridine analog. Although this result is consistent with the notion that O-GlcNAc directly affects the activity of RNA polymerase, transcription factors, or epigenetic regulators (63,64), the observed decrease in labeling may also arise indirectly from a defect in T cell activation, which normally leads to increased RNA synthesis (65). Thus, we repeated this experiment using flow cytometry to enable the analysis of resting T cells.…”
Section: Inhibition Of Ogt Blocks Rna Synthesissupporting
confidence: 85%
“…Both OGT and OGA are important in modulating gene transcription (23). For example, RNA polymerase II is modified by O-GlcNAc (24), and O-GlcNAcylation of RNA polymerase II promotes the formation of the transcriptional preinitiation complex (25); however, for transcriptional elongation to proceed OGA needs to remove the O-GlcNAc to facilitate the phosphorylation of the RNA polymerase II C-terminal tail and elongation (25). O-GlcNAcylation is also important for proper protein translation with alterations to cellular O-GlcNAc levels impinging on the function of the translational machinery (26).…”
Section: Discussionmentioning
confidence: 99%
“…CTD O-GlcNAcylation was originally found on calf thymus RNA pol II and more recently on human pol II (19,20). Edman degradation of calf thymus pol II indicated that both Thr-4 and Ser-5 of the CTD are O-GlcNAcylated (19), whereas serine to alanine substitutions (20) and mass spectroscopy indicated that Ser-5 was O-GlcNAcylated.…”
Section: Minireview: O-glcnac and Epigeneticsmentioning
confidence: 99%
“…it is a pre-initiation species or a post-elongation species). Focus centered on pol II␥ acting before initiation after finding that OGT and OGA catalytic activity are necessary for transcription in vitro and that inhibition of these enzymes blocks transcription during pre-initiation complex assembly (20). OGT can be detected at promoters and immunoprecipitated with pol II (20).…”
Section: Minireview: O-glcnac and Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation